Impossible escape : a true story of survival and heroism in Nazi Europe - Sheinkin, Steve (Roaring Brook Press, 2023)
It is 1944. A teenager named Rudolph (Rudi) Vrba has made up his mind. After barely surviving nearly two years in the Auschwitz concentration camp in Poland, he knows he must escape. Even if death is more likely. Rudi has learned the terrible secret hidden behind the heavily guarded fences of concentration camps across Nazi-occupied Europe: the methodical mass killing of Jewish prisoners. As trains full of people arrive daily, Rudi knows that the murders won't stop until he reveals the truth to the world--and that each day that passes means more lives are lost. Lives like Rudi's schoolmate Gerta Sidonová. Gerta's family fled from Slovakia to Hungary, where they live under assumed names to hide their Jewish identity. But Hungary is beginning to cave under pressure from German Nazis. Her chances of survival become slimmer by the day. The clock is ticking. As Gerta inches closer to capture, Rudi and his friend Alfred Wetzler begin their crucial steps towards an impossible escape. This is the true story of one of the most famous whistleblowers in the world, and how his death-defying escape helped save over 100,000 lives.